Epidemiological profile of leprosy cases in Porto Nacional - Tocantins from 2007 to 2018 - de Aguiar, Daniel Ximenes; Raiol, Sanderson Rodrigo do Nascimento; Costa, Cristiano Ribeiro; de Aquino , Francisco Djailson Muniz; Costa, Nelzir Martins (HSJ, 2020)
Objective: To analyze the epidemiological profile of the population diagnosed with leprosy in the municipality of Porto Nacional, Tocantins. Methods: Cross-sectional, descriptive, quantitative epidemiological survey of registered leprosy cases from January 2007 to August 2018. Data were collected in the Notifiable Diseases Information System submitted to descriptive statistics. Results: 546 leprosy notifications were identified in the studied period. There was a prevalence of males (n = 296 cases; 54.2%), brown skin (n = 389; 71.2%), and the age group of 30 to 39 years (n = 120; 22%). The dimorphic form was predominant, with 260 notifications (47.6%), and the multibacillary type, with 322 cases (59%). The study identified that specialized health centers performed a large number of notifications of the disease (44.7%) and the primary health units in the municipality provided a higher coverage in the detection of this pathology (55.3%). Conclusion: Leprosy is still a public health problem in the municipality of Porto Nacional - TO, although curable and with low recurrence, it is active in the population. Prevention measures, health promotion, multi-professional training, and early diagnosis favor to improve prognosis.